The effects of HIV and smoking on aortic and splenic inflammation. (2nd January 2018) - Longenecker, Chris T.; Sullivan, Claire E.; Morrison, Justin; Hileman, Corrilynn O.; Zidar, David A.; Gilkeson, Robert; O'Donnell, James; McComsey, Grace A.
Abstract : Objective: To determine the association of smoking and HIV status with tissue-specific inflammation measured by 18 flurodeoxyglucose positron emission tomography (PET). Design: A cross-sectional study. Methods: We prospectively enrolled 55 HIV + study participants on stable antiretroviral therapy and 19 age-matched HIV-uninfected controls without known cardiovascular disease. We measured aortic target-to-background ratio (TBR) and spleen standardized uptake values (SUV) 3-h post-FDG, and used regression models to examine the independent association of HIV and smoking status with PET variables. Results: Overall, median (interquartile range) age was 50 (42–55) years; 81% were men and 54% were current smokers (median 0.5 packs/day, 25 pack-years]. Median CD4 + of HIV + study participants was 690 cells/ml and 88% had HIV-1 RNA less than 20 c/ml; 43% were on a protease inhibitor. In fully adjusted models, HIV was associated with 0.16 (95% confidence interval 0.04–0.27; P  = 0.009) higher aortic TBR, whereas current smoking was marginally associated with a lower TBR [−0.11 (95% confidence interval −0.23 to 0.01); P  = 0.07]. Spleen SUVmean was not associated with HIV or smoking, and there was no evidence for an HIV * smoking interaction for aortic or spleen models (all P  > 0.1). Spleen SUVmean was positively associated with biomarkers of inflammation and coronary artery calcium, but adjustment for traditional cardiovascular disease risk factors attenuated these relationships. Conclusion: The FDG-PET study of HIV + study participants suggests that HIV is associated with increased aortic inflammation independent of traditional risk factors, but smoking is not. Future studies should continue to explore the mechanistic roles of smoking and inflammation at various stages of clinical and subclinical atherosclerotic vascular disease in HIV.